(untitled) (Bangladesh Journal of Animal Science, 2018)
The experiment was conducted to investigate the present status and potentialities of organic goat production in Mymensingh district of Bangladesh through field survey. The data were collected through an interview schedule personally from 45 respondents in 3 villages of Bhaluka upazila who were involved in goat production. Parameters studied were check list for organic goat production likes origin, feeds and fodder, breeding, health care, living conditions and record keeping of livestock and factors related to organic goat production. In this study, about 100% goats were indigenous in origin. Among the farmers, 96% farmers used roadside grass and tree leaves whereas, only 4% farmers used cultivated fodder which was cultivated in their own land. 85% farmers used mixed feed which prepared by themselves. However, only 11% farmers used vitamin mineral supplementation.100% farmers used natural breeding method for goat breeding. About 91, 80 and 100% farmers practiced vaccination, deworming and castration method, respectively. About 84% farmers did not use hormone, antibiotic and growth promoter and 67% farmers removed sick or injured animals from healthy stock. About 100% farmers allowed access to outdoor and fallow land throughout the year. Only 31% farmers reared male and female goat separately and 60% farmers kept livestock record. In Bangladesh goat are reared in the conventional method where different inorganic substances are used by the farmers There are great potentialities for organic goat production in Bangladesh both for satisfying animal protein requirements and production of quality goat meat. For this, it is a prime importance to find out the present status and explore the potentialities of organic goat production in Bangladesh. Bang. J. Anim. Sci. 2018. 47 (1): 13-20